Small Cities, Big Issues: Reconceiving Community in a Neoliberal Era - Edited by Christopher Walmsley and Terry Kading (Athabasca University Press, 2018)
Small Canadian cities confront serious social issues as a result of the neoliberal economic restructuring practiced by both federal and provincial governments since the 1980s. Drastic spending reductions and ongoing restraint in social assistance, income supports, and the provision of affordable housing, combined with the offloading of social responsibilities onto municipalities, has contributed to the generalization of social issues once chiefly associated with Canada's largest urban centres. As the investigations in this volume illustrate, while some communities responded to these issues with inclusionary and progressive actions others were more exclusionary and reactive-revealing forms of discrimination, exclusion, and "othering" in the implementation of practices and policies. Importantly, however their investigations reveal a broad range of responses to the social issues they face. No matter the process and results of the proposed solutions, what the contributors uncovered were distinctive attributes of the small city as it struggles to confront increasingly complex social issues. If local governments accept a social agenda as part of its responsibilities, the contributors to Small Cities, Big Issues believe that small cities can succeed in reconceiving community based on the ideals of acceptance, accommodation, and inclusion.